Upaya Guru BK dalam Mengatasi Perilaku Misbehavior Siswa - ,Jihan Nazla; Ali Daud Hasibuan (Fakultas Tarbiyah IAI Nasional Laa Rooiba, 2023)
One of the good classroom management is the creation of a conducive class or class that is able to show that children can listen to every explanation or direction from the teacher. However, we often find that there are children who should be able to listen or mingle with others, but they show things that might interfere with learning in class. Disruptive behavior by children is behavior that does not support the learning process which is carried out repeatedly by students in class and comes in various forms according to the conditions of each class. Disruptive behavior is a child problem in class that cannot be taken lightly. Strategies for providing an effective learning environment include not only making good use of class time, creating an atmosphere conducive to interest in learning, and providing opportunities for activities that engage students' minds and imaginations, but also more importantly preventing and responding to student behavior that annoying in class. Many teachers who teach in class tend to ignore or think that this is normal child behavior or that the teacher doesn't really know how to deal with this disruptive behavior. For this reason, class teachers can take various actions to reduce disruptive behavior in class through various approaches, namely behavioristic, cognitive and humanistic. Abstract: Handling, Behavior, Cognitive, Humanistic